Proximity-based proteomics (BioID) uncovers the Rho GTPase interactome in kidney podocytes - Ibrahim, Sajida; Matsuda, Jun; Nurcombe, Zachary W.; Boulais, Jonathan; Aoudjit, Lamine; Foxman, Emily; Kazan, Cyril; Suzuki, Soichiro; Leclerc, Simon; Shimada, Naoyuki; Kitzler, Thomas; Coté, Jean-François; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPodocyte injury causes proteinuria. Rho GTPases play critical roles in regulating the podocyte cytoskeleton, and their alteration leads to foot process effacement. Yet, their signaling networks remain poorly understood.MethodologyTo address this, we mapped the interactomes of RhoA, Rac1, and Cdc42 in human podocytes using proximity-dependent biotin identification (BioID) labeling.Results and discussionOur BioID analysis detected a total of 1927 interactions with AvgP ≥ 0.95. Approximately 50% of the interactions are unique to podocytes compared to interactions in HEK293 and HeLa cells, with enrichment in pathways related to cell adhesion and shape organization. KIAA1522 emerged as a Rac1/Cdc42 interactor. KIAA1522 knockout reduced cellular projection formation in podocytes, while KIAA1522 knockdown in zebrafish resulted in foot process effacement. Additionally, we identified 20 guanine nucleotide exchange factors (GEFs), with 11, 8, and 5 interacting with RhoA, Rac1, and Cdc42, respectively. Analysis of public scRNA-seq datasets identified RhoA regulators as highly enriched in podocytes. Knockout of most RhoA GEFs reduced RhoA activity, with ARHGEF12 having the greatest effect. Our study defined key upstream regulators and downstream effectors of Rho GTPases in podocytes, identifying KIAA1522 as a novel Cdc42 effector and ARHGEF12 as a key RhoA regulator.